Pengaruh Pemberian Beberapa Konsentrasi Antitranspiran Chitosan Terhadap Kesegaran Bunga Teratai (Nymphaea caerulea) - DARMAYUDA, I MADE DWI; ASTAWA, I NYOMAN GEDE; SUKEWIJAYA, I MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.1, Januari 2018, 2018)
Effect of Several Concentrations of Antitranspirant Chitosan on Freshness of Nymphaea Flower (Nymphaea caerulea) The purpose of this research was to determine the optimum concentration of Chitosan in extending the freshness of the nymphaea flower. This research was conducted at Postharvest Engineering Laboratory, Faculty of Agricultural Technology, Udayana University Denpasar from November 2016 until January 2017. The design used was completely random design (RAL). This research consist was of one factor that was chitosan with five namely C0 = Chitosan 0 ml/L, C1 = chitosan 2,5 ml/L, C2 = chitosan 5 ml/L, C3 = chitosan 7,5 ml/L, C4 = chitosan 10 ml/L. Each treatment were consisted of five replicates, so the experiment was consisted of 25 experimental units and each experimental unit was consisted of two nymphaea stem cut. There were four observed variables, namely weight loss, total absorbed water, duration of freshness of interest, and respiration rate. The results showed that chitosan treatment had a very significant effect on all observed variables. Treatment of C4 (Chitosan 10 ml / L) was not optimum in extending the freshness of the nymphaea, but the concentration of 10 ml / L was the longest concentration to extend the nymphaea flower concentration compared to the other concentration (4.6 days).